Interventional management of necrotizing pancreatitis: an Australian experience. Issue 9 (24th November 2015) - Woo, Shanan; Walklin, Ryan; Wewelwala, Chandika; Berry, Roger; Devonshire, David; Croagh, Daniel
Abstract: Background: The interventional management of necrotizing pancreatitis has evolved from early open surgery to delayed endoscopic or percutaneous intervention. However, few studies have directly compared the three treatment modalities. We aim to compare the outcomes of patients who had endoscopic, percutaneous or surgical interventions for necrotizing pancreatitis at our institution. Methods: This is a retrospective cohort study of patients who had interventions for necrotizing pancreatitis at our institution from 2005 to 2014. Primary outcome was length of stay (LOS); secondary outcomes were complication rate and number of procedures required for resolution of necrosis. Results: Thirty patients were included. Mortality rate was 13% (four patients). Median LOS and time to intervention was 88 and 28 days, respectively. There were no significant differences in the computed tomography severity indices and 48‐h C‐reactive protein levels among the three groups. Initial endoscopic intervention was associated with a median LOS of 62 days compared with 101 days in the percutaneous group and 91 days in the surgical group ( P = 0.04). There were higher rates of pancreatic fistulae (40%) ( P = 0.012) and new onset diabetes (30%) ( P = 0.046) in the surgical group. Median number of procedures was similar among the three groups. Median LOS for patients with delayed intervention (fourth to sixth week of pancreatitis) was 66 days, compared with 137 days in patients with early intervention (first to third week) and 104 days in patients with late intervention (seventh week onwards) ( P ≤ 0.001). Conclusion: A delayed, endoscopy first approach appears to be a reasonable strategy as it is associated with decreased LOS and low complication rate.